OP0141 No Signs for Direct Bone Formation or Endochondral Ossification at the Entheses in Facet Joints from Ankylosing Spondylitis Patients. (23rd January 2014) - Bleil, J.; Syrbe, U.; Maier, R.; Sieper, J.; Appel, H.
Abstract : Background: The mechanisms leading to new bone formation and ankylosis in zygapophyseal joints of patients with ankylosing spondylitis (AS) are not well understood. Despite the hypothesis that the enthesis is the primary disease localization in SpA [1 ], immunohistochemical analysis of bone and cartilage metabolism in the entheses of diarthrodial joints like facet joints have not been performed yet. Objectives: Immunohistochemistry, using different markers indicating anabolic and catabolic processes within cartilage and bone, was performed in order to detect possible entheseal new cartilage and bone formation in facet joints of patients with AS. Methods: An immunohistochemical analysis of beta-Catenin, Dickkopf-1 (DKK-1), Sclerostin, SRY(sex determining region Y)-box 9 (Sox9), runt-related transcription factor 2 (Runx2), matrix metalloproteinase 3 (MMP3), matrix metalloproteinase 13 (MMP13), collagen type 10 (COL10), bone morphogenetic protein 2 and 7 (BMP-2 and BMP-7) and Osteocalcin (OC) was performed. Facet joints from 10 patients with AS, 11 with osteoarthritis (OA) and 10 controls (CO, autopsies without spinal diseases) were analyzed at the enthesial sites. Results: A significantly higher expression of intracellular ß-catenin (p=0.6985), DKK-1 (p=0.9476), Sclerostin (p=0.9468), BMP-7 (p=0.5545), COL10 (p=0.7039), MMP3 (CO>AS p=0.0020) or OC (p=0.1740) in patients with AS in comparison to controls was not observed at enthesial sites. Only the frequency of Runx2 (p=0.0006) and MMP13 (p=0.0378) expressing cells at the entheses was significantly higher in AS than in controls, while Sox9 (AS vs. CO p=0.0097; AS vs. OA p=0.0045) and BMP-2 (AS vs. CO p=0.0016; AS vs. OA p=0.0021) were expressed even less in AS. All markers were significantly (MMP13 p=0.0017; OC p=0.0003; Sox9 p=0.0045; Sclerostin p=0.0180; DKK-1 p=0.0183; BMP-2 p=0.0021) or at least slightly (Runx2 p=0.1568; MMP3 p=0.3222; ß-catenin p=0.0615; BMP-7 p=0.2512; COL10 p=0.3560) lower expressed in AS compared to OA. Conclusions: The analysis for parameters of endochondral ossification (like the hypertrophy markers Runx2, COL10 and MMP13) or of the wnt pathway (ß-catenin, DKK-1 and Sclerostin) revealed the absence of further signs for direct bone formation or endochondral ossification at the entheses in AS facet joints. References: McGonagle D, Gibbon W, Emery P. Classification of inflammatory arthritis by enthesitis. Lancet. 1998 Oct 3; 352(9134):1137-1140. Disclosure of Interest: J. Bleil: None Declared, U. Syrbe: None Declared, R. Maier: None Declared, J. Sieper Consultant for: Roche and Sanofi, H. Appel: None Declared